Bioprocessed Brewers' Spent Grain Improves Nutritional and Antioxidant Properties of Pasta - Rosa Schettino; Michela Verni; Marta Acin-Albiac; Olimpia Vincentini; Annika Krona; Antti Knaapila; Raffaella Di Cagno; Marco Gobbetti; Carlo Giuseppe Rizzello; Rossana Coda (MDPI AG, 2021)
Brewers' spent grain (BSG), the by-product of brewing, was subjected to a xylanase treatment followed by fermentation with Lactiplantibacillus plantarum PU1. Bioprocessed BSG has been used as ingredient to obtain a fortified semolina pasta which can be labeled as "high fiber" and "source of protein" according to the European Community Regulation No. 1924/2006. Compared to native BSG, the use of bioprocessed BSG led to higher protein digestibility and quality indices (essential amino acid index, biological value, protein efficiency ratio, nutritional index), as well as lower predicted glycemic index. Bioprocessing also improved the technological properties of fortified pasta. Indeed, brightfield and confocal laser scanning microscopy revealed the formation of a more homogeneous protein network, resulting from the degradation of the arabinoxylan structure of BSG, and the release of the components entrapped into the cellular compartments. The extensive cell wall disruption contributed to the release of phenols, and conferred enhanced antioxidant activity to the fortified pasta. The persistence of the activity was demonstrated after in vitro-mimicked digestion, evaluating the protective effects of the digested pasta towards induced oxidative stress in Caco-2 cells cultures. The fortified pasta showed a peculiar sensory profile, markedly improved by the pre-treatment, thus confirming the great potential of bioprocessed BSG as health-promoting food ingredient.